+0  
 
0
18
1
avatar

Please helppppp ASAP!!!!!

 Jan 14, 2020
 #1
avatar+17893 
+1

f(x)  =  5 / (x - 2)

g(x)  =  2x / (x2 - 4)

 

f(x) + g(x)  =  5 / (x - 2)  +  2x / (x2 - 4)     =  5 / (x - 2)  +  2x / [ (x - 2)(x + 2) ]

                                     =  [ 5(x + 2) ] / [ (x - 2)(x + 2) ]  +  2x / [ (x - 2)(x + 2) ]

                                     =  [ 5(x + 2) + 2x ] / [ (x - 2)(x + 2) ]

                                     =  [ 5x + 10 + 2x ] / [ (x - 2)(x + 2) ]

                                              =  [7x + 10] / [ (x - 2)(x + 2) ]

 

(f + g)(-1)  =  [ 7 · -1 + 10 ] [ (-1 -2)(-1 + 2) ]  =  3 / -3  =  -1

 
 Jan 15, 2020

14 Online Users

avatar
avatar